A single educational intervention on heart failure self-care: Extended follow-up from a multisite randomized controlled trial. (17th July 2020) - Deek, Hiba; Noureddine, Samar; Allam, Dalia; Newton, Phillip J; Davidson, Patricia M
Abstract: Background: Heart failure outcomes remain poor, and little is known about the causes and predictors of these outcomes in Lebanon. Aim: The purpose of this article is to report the causes and predictors of the 6- and 12-month readmission and mortality of previously recruited patients to the Family focused Approach to iMprove Heart Failure care In LebanonQualitY intervention (FAMILY) study. Methods: A multi-site block randomized controlled trial in three tertiary medical centers in Beirut. Initially, participants were randomized to either the control or the intervention group. The latter group, with their family caregivers, received heart failure self-care resources and an educational intervention on self-care and symptom management during their index admission. Participants from the FAMILY study were followed up with through phone calls for readmission and mortality at 6 and 12 months following their hospital discharge. Results: A total of 218 (85%) patients were followed up with for this evaluation. There was a significant difference between the intervention group and the control group in terms of mortality at 6 months ( n =18 (16%) versus n =36 (33%); p <0.05) and 12 months ( n =29 (26%) versus n =45 (42%); p <0.05) post the index discharge. Mortality at 6 and 12 months was associated with aging, lower body mass index scores and readmission at 30 days post the index admission. Results of a logistic regression for mortality at 6 months showed hypertensive etiology of heart failure and 30-day readmission to be the only significant predictors. Conclusion: A single session intervention was associated with lower mortality, even after an extended period of time, possibly mediated by other variables. Future studies should be powered for such outcomes while also addressing the cultural needs and literacy levels of the patients using multi-session trials and more frequent follow-ups.